Elevated Ratio of Th17 Cell-Derived Th1 Cells (CD161+Th1 Cells) to CD161+Th17 Cells in Peripheral Blood of Early-Onset Rheumatoid Arthritis Patients. (30th March 2016) - Kotake, Shigeru; Nanke, Yuki; Yago, Toru; Kawamoto, Manabu; Kobashigawa, Tsuyoshi; Yamanaka, Hisashi
Abstract : Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by the destruction of articular cartilage and bone with elevated levels of proinflammatory cytokines. It has been reported that IL-17 and Th17 cells play important roles in the pathogenesis of RA. Recently, plasticity in helper T cells has been demonstrated; Th17 cells can convert to Th1 cells. It remains to be elucidated whether this conversion occurs in the early phase of RA. Here, we tried to identify Th17 cells, Th1 cells, and Th17 cell-derived Th1 cells (CD161 + Th1 cells) in the peripheral blood of early-onset RA patients. We also evaluated the effect of methotrexate on the ratio of Th17 cells in early-onset RA patients. The ratio of Th17 cell-derived Th1 cells to CD161 + Th17 cells was elevated in the peripheral blood of early-onset RA patients. In addition, MTX reduced the ratio of Th17 cells but not Th1 cells. These findings suggest that IL-17 and Th17 play important roles in the early phase of RA; thus, anti-IL-17 antibodies should be administered to patients with RA in the early phase.